2020
DOI: 10.3390/rs12142217
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Ice Phenology of Qinghai Lake from 1980 to 2018 Using Multisource Remote Sensing Data and Google Earth Engine

Abstract: Lake ice, one of the most direct lake physical characteristics affected by climate change, can reflect small-scale environmental changes caused by the atmosphere and hydrology, as well as large-scale climate changes such as global warming. This study uses National Oceanic and Atmospheric Administration, Advanced Very High Resolution Radiometer (NOAA AVHRR), MOD09GQ surface reflectance products, and Landsat surface reflectance Tier 1 products, which comprehensively used RS and GIS technology to study lake ice p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…It was also inferred that the increase in the area of the single selected thermokarst lake mainly depended on the increasing thawing speed caused by high wind speed, and the thawing of ice-rich permafrost and massive ice near the selected thermokarst lake [38]. According to the literature [39], we inferred that wind speed greatly affects the freezing and thawing processes of the thermokarst lakes. The changes in wind speed make the newly appeared ice layer disappear, leading to the repeated freezing-thawing phenomena in the freezing process of the lakes.…”
Section: Influences Of Meteorological Factors On the Total Area Of Thermokarst Lakes In Beilu River Basinmentioning
confidence: 73%
“…It was also inferred that the increase in the area of the single selected thermokarst lake mainly depended on the increasing thawing speed caused by high wind speed, and the thawing of ice-rich permafrost and massive ice near the selected thermokarst lake [38]. According to the literature [39], we inferred that wind speed greatly affects the freezing and thawing processes of the thermokarst lakes. The changes in wind speed make the newly appeared ice layer disappear, leading to the repeated freezing-thawing phenomena in the freezing process of the lakes.…”
Section: Influences Of Meteorological Factors On the Total Area Of Thermokarst Lakes In Beilu River Basinmentioning
confidence: 73%
“…They reported that the FUS, FUE, BUS, BUE, CFD and ICD shifted on average by 0.73, 0.34, −1.66, −0.81, −1.91, −2.21 d/a respectively. Qi et al (2020) used AVHRR, MODIS, and Landsat data to extract the LIP of Qinghai lake (China, area of 4294 km 2 ) for the period 1980-2018. They estimated a shift of 0.16, 0.19, −0.36, and −0.42 d/a for FUS, FUE, BUS and BUE respectively, also pointing towards progressively later freeze-up and earlier break-up.…”
Section: Lip Trend Analysis Studiesmentioning
confidence: 99%
“…1 and Table B.8 (Appendix B). While most of the earlier works (Gou et al, 2015;Qi et al, 2019Qi et al, , 2020Yao et al, 2016) on long time-series monitoring of lake ice with MODIS concentrated on larger lakes, many lakes that freeze are actually small-or medium-sized mountain lakes, especially outside the (sub-)Arctic regions. The lakes we analyse are relatively small in area (0.78 -11.3 km 2 ), representative for this category.…”
Section: Study Areamentioning
confidence: 99%
“…Previous studies have documented significantly earlier ice break-up dates and decreasing ice duration since the 1950s at the hemispheric scale [11,12], and in many typical regions such as in the pan-Arctic [4,[13][14][15][16] and the Tibetan Plateau [17][18][19][20][21][22]. The earlier ice break-up dates and decreasing ice durations lead to the increase in spring meltwater and runoff and, subsequently, to changes to the global hydrological cycle.…”
Section: Introductionmentioning
confidence: 99%